(untitled) (Eurasian Research Bulletin, 2024)
In this article, the main goal of guiding students to the profession is to help each student individually to choose the field of profession or technological activity in a basic and correct way, the question of the important tasks of pedagogues in guiding students to the profession is discussed. drawn up.